Pelaksanaan Kebijakan Penurunan Tarif Pajak Final UMKM di Kantor Pelayanan Pajak Pratama Jakarta Penjaringan - Andrianto Setyoadi (Jurnal Pajak Vokasi (JUPASI), 2021)
This study aims to analyze the implementation of the policy to reduce the MSME’s final tax rate at the Jakarta Penjaringan Tax Office. This research is a qualitative research with data collection techniques through interviews, observation and using written documents. The results showed that the implementation of the policy has several weaknesses, namely the database so that the application of sanctions has not been fully implemented. In addition, the awareness of MSME actors about taxation is still very low. Socialization is not effective because it is only in writing so that it has not been able to improve the skills of MSME players in carrying out tax obligations.